On screen directing - Dmytryk, Edward (Routledge, 2019)
"With On Screen Directing, renowned filmmaker Edward Dmytryk distills a lifetime of experience as a director into a dozen short essays on the craft of directing, spanning every stage of the filmmaking process, from screenwriting, preproduction and casting to set design, postproduction, and promotion. Originally published in 1984, this reissue of Dmytryk's classic directing book includes a new critical introduction by Bette Gordon and Eric Mendelsohn, as well as chapter lessons, discussion questions, exercises, and a glossary"--